Faktor-Faktor yang Mempengaruhi Kurangnya Minat Baca Siswa dalam Pembelajaran Bahasa Indonesia di Sekolah Dasar - Rosalina Puspasari Dewi; Ruky Ramadhani; Reska Amzi Rahayu; Afriza Media; Ari Suriani (Lembag, 2025)
The low interest in reading of students in elementary school is a serious problem that has a direct impact on the quality of learning, especially in Indonesian subjects. This article aims to identify and analyze various factors that affect student’s low interest in reading through a literature review approach. The results of the analysis showed that these factors included limited literacy facilities, lack of active role of teachers and parental support, negative influence of digital technology, less attractive teaching methods, and low motivation and reading habits of students. The impact of low interest in reading includes difficulty understanding reading, weak vocabulary mastery, and low learning achievement. This article also reviews various strategies that teachers can do to increase student’s reading interest, such as reading habits, the use of storytelling methods, reading corners, the use of technology, as well as thematic approaches and creative literacy programs. Cooperation between schools, families, and communities is needed to create a literacy ecosystem that supports the growth of reading interest from an early age.